Вивчення уніфікації процесу розробки продуктів за допомогою дизайн-систем - Тира, М. (My University, 2020)
Currently, companies often develop various products, and one of the goals in their creation is to unify their visual style to simplify working with them and make products more recognizable among consumers. This can be done by creating a design system for the company
Keywords: уніфікація процесу; розробка продуктів; дизайн-система